Nucleic-Acid Based Lateral Flow Strip Biosensor via Competitive Binding for Possible Dengue Detection - Enriquez, Erwin P (Archīum Ateneo, 2012)
A low-cost, simple, rapid and selective nucleic-acid based lateral flow strip biosensor (LFSB) for possible dengue viral RNA detection is described in this study. The detection is based on competitive binding, where gold nanoparticles (AuNPs), with average size of ~10 nm confirmed using UV-Vis, TEM and AFM images, are used as visualizing agents. These are bioconjugated with DNA which competitively binds with its complementary strand either in the sample or in the test line of the LFSB. The detection scheme reduces the number of probes which effectively lowers the cost for the design of the test strip. The whole test took less than five minutes to complete and a red line signifies a negative result, while the absence of the line signifies a positive result. Quantification of the intensity of the red band reveals proportionality of the color to the amount of DNA present in the sample. The visual limit of detection of the LFSB is 10-7 M. It demonstrates selectivity in a blood matrix and selectivity over a synthetic Influenza. This study brings us closer to an amplification-free, point-of-care method for dengue detection.